Assessing The Reliability Of Human Social Scoring System And Its Wireframing: A Scientific Study In The Realm Of Human-Computer Interaction - Khalid, Javaria; Abbas, Aneela; Akbar, Rida; Javed, Muhammad Ali; Ijaz, Rabbia; Khalid, Amna; Ali, Aminah; Faseeh, Abdullah; Mouqadas, Faiza (Migration Letters, 2024)
Social interaction lies at the heart of any society, driven by mutual influences among individuals. An innovative concept, "The Human Social Scoring System (HSSS)," has been proposed to establish a social ranking system that assesses in- dividuals’ social conduct and assigns them scores. Today, various products, ser- vices, apps, movies, and more are reviewed and rated to inform decision-making. This research introduces the concept of scoring individuals, which facilitates the formation of opinions about their social standing. The study’s primary objective is to investigate if a person’s score or rank can impact opinion formation. Do indi- viduals rely on such scores for decision-making? What are the concerns regarding the credibility of reviewers and the review platforms? This research also explores the correlation between online reviews and the reliability of HSSS. To this end, a questionnaire was designed to evaluate the significance, reliability, credibility, and correlation of HSSS, with data collected from 265 diverse-age participants (49 % males and 51 % females). Various analysis techniques were used to interpret the data, including ANOVA (analysis of variance), Standard Aggregate Averages, Z-Test, and Pearson correlation. The Z-Test results indicate significant support for HSSS among males and females at a significance level of α=0.05. The Post Hoc test further reveals that support for HSSS is solid among the 31-40 age group. To assess the feasibility of the concept, students were selected as test participants. A detailed wireframe was designed to score and rank them based on personal, professional, and educational behavior. The results strongly endorse the research objectives and align with previous literature.